IMPORTANCE OF SPECIAL COORDINATING CAPABILITIES IN THE GOAL SHOT OF U-12 FOOTBALL PLAYERS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Soccer is a sport practiced worldwide, being a fundamental part of its practice at an early age, oneof its main foundations is the shot at goal, which is the technical action that involves the throwingof the ball into the goal of the opposing team, which can run with the lower extremities, trunk andhead. This action is directly related to coordinative capacities; which are an important element informative soccer training, being fundamental in this research, to establish as an objective, thebase of the importance of training special coordination skills in shooting at goal in U-12 soccerplayers. The methodology was based on a theoretical review study, which uses methods such asanalytical - synthetic for the processing and analysis of information, as well as inductivedeductiveto go from the specific, such as the shot at the door, to the general As is thecoordinative development of the athlete in the execution of the technique of shooting at the door,the type of investigation is documentary, through which an analysis of the information obtainedfrom secondary data is established. Among the fundamental findings it was possible to determinethat the different authors determine in their studies that coordination exercises enhance thetechnique of children at an early age, therefore, they improve aspects such as control, stabilityand shooting at goal.